Pengaruh Model Pembelajaran Self-Dirscted Learning (SDL) Terhadap Keterampilan Menulis Teks Narasi Pada Siswa Kelas IV SD Negeri 110 Palembang - Deacika Destari, Almira; Hermansyah,; Mega Prasrihamni, (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing skills are the ability to convey ideas, information, or feelings clearly and structurally through written language. Low student engagement in inappropriate learning processes results in poor narrative writing skills. Difficulties in generating ideas, lack of motivation, and unfamiliarity with sharing personal experiences are contributing factors. This study aims to determine the effect of the self-directed learning (SDL) model on the narrative writing skills of fourth-grade students at SD Negeri 110 Palembang in the Indonesian language subject. The self-directed learning (SDL) model involves students as the main actors, while the teacher acts as a facilitator. The research method used a quasi-experimental design with a Posttest Only Control Design. The sample consisted of class IV A as the control group and class IV C as the experimental group. Data were collected through written tests. The analysis results showed a significant difference between the experimental and control groups. The average posttest score of the experimental class was 78.23, while the control class scored 48.51. The significance value (2-tailed) was 0.000 < 0.05, thus Ho is rejected and Ha is accepted. It is concluded that the self-directed learning model has a significant effect on narrative writing skills compared to conventional learning.